Exploring the synthesis and impact of end‐functional poly(3‐hexylthiophene). Issue 7 (7th February 2015) - Handa, Nisha V.; Serrano, Abigail V.; Robb, Maxwell J.; Hawker, Craig J.
ABSTRACT In recent years, end‐functional poly(3‐hexylthiophene) (P3HT) has proven to be instrumental in the continued development and innovation within the broad conjugated polymer arena, enabling a variety of applications, particularly in organic electronics. The availability of P3HT with controlled molecular weights, low polydispersity, and importantly, a wide range of reactive end‐groups not only serves as a key building block for the preparation of conjugated block copolymers but also facilitates the development of hybrid nanocomposite materials via inorganic surface modification strategies. This Highlight focuses on the synthetic approaches to end‐functional P3HT and the impact of these systems in emerging technologies. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 831–841